Bioactive heterocyclic compound classes : agrochemicals - Lamberth, Clemens; Dinges, Jurgen (Weinheim : Wiley-VCH ; Chichester : John Wiley [distributor], 2012)
This volume presents important agrochemical pesticides. Each of the around 20 chapters covers in a concise manner one class of heterocycles, clearly structured as follows:* Structural formulas of most important examples (market products)* Short background of history or discovery* Typical syntheses of important examples* Mode of action* Characteristic biological activity* Structure-activity relationship* Additional chemistry information (e.g. further transformations, alternative syntheses, metabolic pathways, etc.)* References. A valuable one-stop reference source for researchers in academia and.
Includes bibliographical references and index.
Print version record.
Keywords: Heterocyclic compounds; Agricultural chemicals; SCIENCE -- Chemistry -- Organic; Agricultural chemicals; Heterocyclic compounds; Electronic books